Competition Policy for Regulated Utility Industries in Britain. - Nuttall, R; Vickers, J (Department of Economics (University of Oxford), 1996)
The main section of the paper analyzes the principles and practice of competition policy for utilities under six headings: price discrimination and cross-subsidy; oligopolistic behaviour; mergers and takeovers; vertical structure; network access pricing; and historical entry barriers. The conclusion discusses proposals for the reform of competition policy for utilities.